Cancer Metastasis - Basbinar, Yasemin; Calıbası-Kocal, Gizem (IntechOpen, 2018)
Metastasis of cancer cells from primary tumor site to secondary locations is considered a late event in multistep tumorigenesis, and causes most cancer-related mortality. The process from the spreading of cancer cells to the seeding of newly formed tumor colonizations is governed by sequential events, including local invasion, intravasation into stroma and blood vessels, survival in circulation, extravasation, and colonization at secondary tumor sites. Cancer research provides information on the fate of metastatic cancer cells in each sequential movement or heterogeneous tumor microenvironment. However, the complexity of this mechanism remains the most stringent concept of cancer management. This book provides information for cancer researchers on metastatic phenotypes of cancer cells, and diverse promoting factors and molecular mechanisms of metastasis.